Gregor the Overlander - Collins, Suzanne (Collins, Suzanne. Underland chronicles, 2004)
When eleven-year-old Gregor and his two-year-old sister are pulled into a strange underground world, they trigger an epic battle involving men, bats, rats, cockroaches, and spiders while on a quest foretold by ancient prophecy.